Validation of Research Work on Traction Type Hydrokinetic Fluid Coupling: A Comparative Study of Theoretical and Practical Power Ratings - Deep R. Prajapati; H. G. Katariya; V. H. Chaudhari; L. A. Nakrani; A. B. Prajapati (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study investigates the performance of hydrodynamic fluid couplings by comparing theoretical power ratings, derived from established models, with practical ratings across a range of industrial coupling sizes and speeds. Building on the foundational work of Rolfe, G. H. (1968) the theoretical framework employs geometric and fluid dynamic principles to calculate power transmission, accounting for slip, vortex flow, and oil properties. Experimental data from a specific fluid coupling at maximum oil filling reveals close alignment between theoretical and practical ratings, with percentage differences consistently minimal across tested conditions. Further analysis across standard sizes at various speeds reinforces this trend, with the largest discrepancies remaining small relative to overall ratings. These findings validate the predictive accuracy of the theoretical model, confirming its applicability for real-world engineering design. The results also align with hydrodynamic principles, such as the relationship between power and speed, and highlight the reliability of fluid couplings for smooth, efficient power transmission in industrial applications.
Keywords: Hydrokinetic fluid coupling; theoretical power rating; slip; smooth power transmission; vortex flow; partially filled coupling; Nomenclatures